تعرض الشباب الجزائري للبرامج الحوارية لقناة الجزيرة الفضائية - مجيدي, رميسة; قيه, هاجر (جامعة الوادي - University of Eloued, 2022)
Through this work the game is presented as a powerful educational means and goes from its influence and its educational interest for the learners and demonstrates how to use it in the practice of a foreign language which is French. The questionnaire presented in our thesis confirms the fact that the game occupies an important place in the teaching as well as the experimentation of the ludic activity and affirms that the pupils are more motivated when using the game. Our work is divided into two phases, a first theoretical one which presents the teaching methods and the notions of the game and its interest in language class, a second so-called practical part: The questionnaire for teachers of the middle level on the role of playful activities in the classroom and ends with an experimentation of playful activity in the middle class of first year
مذكرة ماستر إعلام وإتصال
Keywords: pedagogy, fun activity, game, learning, foreign language